Effective semi-fed-batch saccharification with high lignocellulose loading using co-culture of Clostridium thermocellum and Thermobrachium celere strain A9 - Nhim, Sreyneang; Baramee, Sirilak; Tachaapaikoon, Chakrit; Pason, Patthra; Ratanakhanokchai, Khanok; Uke, Ayaka; Ceballos, Ruben Michael; Kosugi, Akihiko; Waeonukul, Rattiya (Frontiers in Microbiology, 2025)
Maximizing saccharification efficiency of lignocellulose and minimizing the production costs associated with enzyme requirements are crucial for sustainable biofuel production. This study presents a novel semi-fed-batch saccharification method that uses a co-culture of Clostridium thermocellum and Thermobrachium celere strain A9 to efficiently break down high solid-loading lignocellulosic biomass without the need for any external enzymes. This method optimizes saccharification efficiency and enhances glucose production from alkaline-treated rice straw, a representative lignocellulosic biomass. Initially, a co-culture of C. thermocellum and T. celere strain A9 was established with a treated rice straw loading of 150 g/l, supplemented with Tween 20, which enhanced enzymes stability and prevented unproductive binding to lignin, achieving a remarkable glucose concentration of up to 90.8 g/l. Subsequently, an additional 100 g/l of treated rice straw was introduced, resulting in a total glucose concentration of up to 140 g/l, representing 70.1% of the theoretical glucose yield from the 250 g/l treated rice straw load. In contrast, batch saccharification using an initial substrate concentration of 250 g/l of alkaline-treated rice straw without Tween 20 resulted in a glucose concentration of 55.5 g/l, with a theoretical glucose yield of only 27.7%. These results suggest that the semi-fed-batch saccharification method using co-cultivation of C. thermocellum and T. celere strain A9, supplemented with Tween 20 is an efficient microbial method for saccharifying high-concentration biomass. Moreover, this approach effectively manages high solids loading, optimizes efficiency, and reduces the need for external enzymes, thus lowering production costs and simplifying the process for industrial applications.